The Influence of Flood Disasters on Economic Growth and Poverty in Indonesia - Ilyas, Indra Suryadi; Rahardi, Catur Susilo; Kurniawan, Andi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This research examines and analyzes the influence of flood disasters on economic growth and poverty in Indonesia. The study has compiled flood data from government agencies for the period of 2014-2022, especially from the Indonesian National Statistics Authority and the National Agency for Disaster Management. Using the quantitative method, this study has employed Full Generalized Least Square to analyze the flood data further and studied their impact on economic growth. Natural disasters have disrupted critical economic activities, including investment and tourism, and certainly affect employment opportunities. This study underscored the importance of strategic disaster managements that deal with social and economic issues, namely supervision and control, socio-economic strengthening, hydrological and preparedness information systems, disaster resilience infrastructure, spatial planning, and risk mapping, as well as forest and land rehabilitation. It is expected that such government interventions could enhance the reciprocal synchronization of data and the information needed, which is crucial to equalizing the components of Hazard, Capacity, and Vulnerability, especially between Ministries and institutional partners. Moreover, optimizing the analysis of regional development projections and spatial planning is necessary. It includes the use of more comprehensive data and information regarding existing disaster management programs and their implementation. By this, a comprehensive analysis can be carried out and investment needs can be identified. This also includes consideration of climate change aspects in disaster hazard analysis. There is still a need to synchronize flash flood disaster hazard data into analysis, as well as synchronize and share data between both parties for capacity and vulnerability components.